A battery separator capable of in-situ regulating polarization strength and its preparation method and application

By evaporating polar solvents induced dipole flips in the PVDF molecular structure, a β-phase PVDF coating with high spontaneous polarization strength is formed, which solves the problems of low β-phase conversion efficiency and high preparation cost in the prior art, and achieves efficient preparation and performance improvement of battery separators.

CN115911750BActive Publication Date: 2025-03-21HESHAN DONGYAO NEW MATERIAL TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202211469110.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-22
Publication Date
2025-03-21
Estimated Expiration
2042-11-22

AI Technical Summary

Technical Problem

The existing PVDF and its copolymer-coated battery separator technology has problems such as low β-phase conversion efficiency, high preparation cost and complex process, making it difficult to effectively improve the electrochemical performance of the battery.

Method used

The dipoles in the PVDF molecular structure are induced to flip when recrystallized by using volatile polar solvents to form a β-phase PVDF coating with dipoles arranged in a directional arrangement and a high spontaneous polarization intensity. The performance of the coating is optimized by controlling the amount and number of sprays.

Benefits of technology

It has achieved efficient preparation of a hollow network structure PVDF coating with a ratio of more than 80% β, which has improved the ferroelectric and piezoelectric properties of the diaphragm, and significantly improved the battery's magnification capacity and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115911750B_ABST
    Figure CN115911750B_ABST
Patent Text Reader

Abstract

The present invention discloses a battery separator capable of in-situ regulating polarization strength, and a preparation method and application thereof, wherein a solution containing polyvinylidene fluoride-based copolymer powder is coated on the surface of a base film to obtain a separator having a polymer coating on the surface; a volatile polar solvent is then sprayed on the surface of the polymer coating, and the polar solvent is evaporated to obtain the separator. The battery separator comprises a base film and a PVDF-based ferroelectric polymer coating, wherein the proportion of the β phase in the entire PVDF crystalline phase reaches more than 80%, and the PVDF is a hollow network structure, the coating has a porosity of 20% to 80%, and a thickness of 1 to 10 μm. It has excellent ferroelectric and piezoelectric properties, and when used as a lithium battery separator, it can significantly improve the overall rate capacity and cycle stability of the battery. The preparation method is simple, low-cost, energy-saving and environmentally friendly, and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery separators, and more particularly to a battery separator capable of in-situ regulating polarization strength, and a preparation method and application thereof. Background Art

[0002] As an important electrical energy storage device, batteries are widely used in various fields of production and life. Among them, lithium batteries have high energy storage density and long cycle life. They stand out among all secondary batteries and are widely studied and applied. As an important component of the battery, the diaphragm can not only isolate the positive and negative electrodes to prevent short circuits caused by contact between the positive and negative electrodes, but also carry electrolytes and provide channels for Li+ to migrate inside the battery. At present, lithium batteries mostly use chemically stable polyolefin diaphragms, but due to the poor thermal stability and low electrolyte wettability of polyolefin diaphragms, the battery safety factor decreases and the actual capacity deteriorates.

[0003] In order to solve these problems, existing patented technologies generally improve the safety and electrochemical performance of batteries by coating materials such as polyvinylidene fluoride (PVDF) on the base film. However, these technologies (such as Chinese patents with application publication numbers CN 114665218A and CN114374055A) use PVDF coating to only improve the lyophilicity, mechanical strength or flame retardancy of the separator.

[0004] Polyvinylidene fluoride (PVDF) and its copolymers are functional materials with piezoelectric and ferroelectric properties. Studies have shown that PVDF with a certain polarization strength can significantly improve the electrochemical performance of the battery by adjusting the distribution and migration rate of electrolyte ions. There are five crystalline phases of PVDF: α, β, γ, δ, and λ. Most of the PVDF films prepared by conventional methods are α phase, which does not have piezoelectricity and ferroelectricity, while the polar β phase PVDF films have piezoelectricity and ferroelectricity, with a dielectric constant of 22 to 30. In order to obtain a highly polar β phase PVDF film, the usual practice (such as the Chinese patents with application publication numbers CN 107955196A and CN 114899308A) is to start from the common α phase PVDF film, use stretching, electric field polarization, annealing or high energy irradiation to transform the non-polar α phase crystals into polar β phase crystals, and then rearrange the orientation of the β phase crystals under the action of a strong DC electric field to obtain piezoelectricity. These methods have problems such as harsh conditions, low conversion rate from α phase to β phase, complex process and easy damage to the membrane microstructure.

[0005] In summary, while using PVDF and its copolymers to coat battery separators to improve their mechanical strength and wettability, it is of great significance to prepare PVDF coatings with directional molecular structure and high self-polarization strength through low-cost, simple and efficient methods to further give the separator the function of regulating electrolyte ion migration. Summary of the invention

[0006] In view of this, the present invention provides a battery separator with in-situ adjustable polarization strength to address the defects of the existing PVDF and its copolymer coated battery separator technology, such as low β-phase conversion efficiency and high preparation cost. The battery separator comprises a base film and a PVDF-based ferroelectric polymer coating, wherein the β-phase accounts for more than 80% of the total PVDF crystalline phase, and the PVDF is a hollow network structure, the coating porosity is 20% to 80%, and the thickness is 1 to 10 μm. The battery separator has excellent ferroelectric and piezoelectric properties, wherein the coercive field is 70 to 120 V / μm, and the residual polarization strength is 1 to 5 μC / cm 2 , d 33 The coefficient is -5 to -28 pC / N.

[0007] Another object of the present invention is to provide a method for preparing a battery separator capable of in-situ regulating polarization strength, which method is simple, low-cost, high in production efficiency, and suitable for industrial production.

[0008] Another object of the present invention is to provide an application of a battery separator that can in-situ regulate polarization strength. The battery separator can be used as a lithium battery separator, which enhances the separator's affinity for the electrolyte and utilizes its own ferroelectric and piezoelectric properties to promote the distribution and migration of electrolyte ions, greatly improving the overall rate capacity and cycle stability of the battery.

[0009] In order to achieve the above object, the present invention adopts the following technical solution:

[0010] A method for preparing a battery diaphragm capable of in-situ regulating polarization strength comprises the following steps: coating a solution containing polyvinylidene fluoride-based copolymer powder on the surface of a base film to obtain a diaphragm having a polymer coating on the surface; spraying a volatile polar solvent on the surface of the polymer coating, and waiting for the polar solvent to evaporate to obtain the diaphragm.

[0011] Since the F2-CC-H2 dipole in the smallest structural unit of the PVDF molecule is a polar bond, the present invention utilizes volatile strong polar solvent molecules to induce the dipoles in the PVDF molecular structure to flip during recrystallization as the polar solvent evaporates, ultimately forming a β-phase PVDF coating with directional dipole arrangement and high spontaneous polarization strength.

[0012] As a preferred solution, the volatile polar solvent includes at least one of a hydroxyl-containing volatile polar solvent, a carboxyl-containing volatile polar solvent and an amino-containing volatile polar solvent.

[0013] As a preferred solution, the hydroxyl-containing volatile polar solvent includes at least one of water, methanol, ethanol, n-propanol and isopropanol.

[0014] As a preferred solution, the carboxyl-containing volatile polar solvent includes formic acid and / or acetic acid.

[0015] As a preferred solution, the amino-containing volatile polar solvent includes at least one of ammonia water, methylamine and ethylamine.

[0016] As a preferred solution, the volatile polar solvent is sprayed at least once, and the single spraying amount is 1 to 12 mL / m 2 , more preferably 3 to 10 mL / m 2 .

[0017] The applicant found that the amount of a single spray and the number of sprays can increase the content of the β phase in the product, increase the residual polarization strength, optimize the coercive field, dielectric constant, d 33 The above effect can be achieved by controlling the single spraying amount and spraying times of the volatile polar solvent within a reasonable range.

[0018] When the single spraying amount is too low, it cannot be guaranteed that the volatile polar solvent and the polyvinylidene fluoride based copolymer coating will have uniform and sufficient contact, which makes the β phase generation efficiency relatively reduced; when the single spraying amount is too large, the excess polar solvent will dilute the polyvinylidene fluoride based copolymer coating, thereby destroying the coating thickness and density to a certain extent.

[0019] In addition, when the spraying frequency is once, it is more difficult for the volatile polar solvent to fully induce the rotation of the dipoles of the polyvinylidene fluoride copolymer (that is, the β-crystal phase generation rate is relatively reduced); and too many spraying times will not have much effect on the formation of the β-phase, but will reduce the crystallization time and crystallization strength of the polyvinylidene fluoride copolymer to a certain extent, and also increase the cost of spraying.

[0020] As a preferred solution, the volatile polar solvent is sprayed no less than twice.

[0021] In industrial applications, the number of spraying times can be adjusted according to production efficiency and product quality, preferably 2 to 6 times, more preferably 3 to 5 times.

[0022] When the number of spraying times is greater than one, the preferred spraying method is: spraying the polar solvent again when the surface solvent is nearly completely evaporated.

[0023] As a preferred embodiment, the polyvinylidene fluoride-based copolymer powder includes at least one of polyvinylidene fluoride (PVDF), poly(vinylidene fluoride + chlorotrifluoroethylene) (P(VDF+CTFE)), poly(vinylidene fluoride + co-trifluoroethylene) (P(VDF+TrFE)), poly(vinylidene fluoride + co-hexafluoropropylene) (P(VDF+HFP)) or poly(vinylidene fluoride + trifluoroethylene + chlorofluoroethylene) (P(VDF+TrFE+CFE)).

[0024] As a preferred solution, the mass concentration of the polyvinylidene fluoride based copolymer powder in the solution containing the polyvinylidene fluoride based copolymer powder is 3 to 15%, more preferably 5 to 15%.

[0025] Controlling the mass concentration of the polyvinylidene fluoride based copolymer powder within an appropriate range is beneficial to improving the ferroelectric properties of the coating. When the mass concentration of the polyvinylidene fluoride based copolymer powder is too low, relatively less polyvinylidene fluoride based copolymer is coated on the diaphragm substrate, making it more difficult to effectively utilize the ferroelectricity of the coating to improve battery performance; and when the mass concentration is too high, the polyvinylidene fluoride based copolymer slurry is too thick, making it difficult to evenly coat it on the surface of the diaphragm substrate and forming a dense, thick crystalline layer, which will reduce the porosity of the diaphragm to a certain extent and greatly limit the flow of electrolyte ions.

[0026] As a preferred solution, the solvent in the solution containing the polyvinylidene fluoride-based copolymer powder is at least one of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), and 1,5-dimethyl-2-pyrrolidone.

[0027] As a preferred solution, the preparation process of the solution containing polyvinylidene fluoride based copolymer powder is as follows: mixing polyvinylidene fluoride based copolymer powder with a solvent, heating to 50°C to 80°C and stirring at a constant speed to completely dissolve the polymer powder to obtain a transparent and uniform solution.

[0028] As a preferred solution, the base film includes at least one of a polyethylene film, a polypropylene film, a polyimide film, and a polypropylene / polyethylene composite film.

[0029] As a preferred solution, the solution containing polyvinylidene fluoride based copolymer powder is coated on the surface of the base film by using an adjustable scraper to coat the solution containing polyvinylidene fluoride based copolymer powder on the surface of the base film. The gap width of the adjustable scraper is preferably 10 to 50 μm.

[0030] As a preferred solution, the polar solvent is volatilized by placing the diaphragm at 60-100° C. and drying for 4-10 hours.

[0031] The present invention also provides a battery separator with in-situ adjustable polarization strength, which is prepared by the above method. The battery separator has excellent ferroelectric and piezoelectric properties, wherein the coercive field is 70-120 V / μm, and the residual polarization strength is 1-5 μC / cm 2 , d 33 The coefficient is -5 to -28 pC / N.

[0032] As a preferred solution, the battery separator comprises a base film and a PVDF-based ferroelectric polymer coating, wherein the β-phase crystalline phase in the PVDF-based ferroelectric polymer coating accounts for no less than 80%. The PVDF is a hollow network structure, the coating has a porosity of 20% to 80%, and a thickness of 1 to 10 μm.

[0033] The present invention also provides an application of a battery separator capable of in-situ regulating polarization strength as a lithium battery separator. When the battery separator is used as a lithium battery separator, it can enhance the lyophilicity of the separator to the electrolyte, promote the distribution and migration of electrolyte ions, and significantly improve the overall rate capacity and cycle stability of the battery.

[0034] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0035] (1) The preparation method can flexibly control the ferroelectricity of the polymer, is low-cost, and can quickly and effectively obtain a large-area ferroelectric polymer PVDF coating layer with a β phase and high polarization strength;

[0036] (2) The ferroelectric coating membrane is obtained, which not only strengthens the membrane's affinity for the electrolyte, but also promotes the distribution and migration of electrolyte ions by utilizing its own ferroelectric and piezoelectric properties, thereby enhancing the battery's cycle life and actual discharge capacity.

[0037] (3) When used as a lithium battery separator, it can significantly improve the overall rate capacity and cycle stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0039] Figure 1 The crystalline phase structures of the PVDF-based ferroelectric polymer coating and the PVDF powder raw material in the diaphragm prepared in Example 1, wherein (a) is the PVDF-based ferroelectric polymer coating in the diaphragm prepared in Example 1, and (b) is the PVDF powder raw material.

[0040] Figure 2 Microscopic morphology of the PVDF-based ferroelectric polymer coating on the base membrane in the diaphragm prepared in Example 1.

[0041] Figure 3 1 is the hysteresis loop of the diaphragm prepared in Example 1.

[0042] Figure 4 This is a diagram of the piezoelectricity d33 test device of the diaphragm prepared in Example 1.

[0043] Figure 5 The Zeta potential diagram of the diaphragm prepared in Example 1.

[0044] Figure 6 It is a comparison chart of the first charge and discharge curves of lithium batteries assembled with the diaphragms prepared in Example 1 and Comparative Examples 1 and 2.

[0045] Figure 7 It is a comparison chart of the rate performance of lithium batteries assembled with the diaphragms prepared in Example 1 and Comparative Examples 1 and 2.

[0046] Figure 8 It is a long cycle comparison chart of lithium batteries assembled with the diaphragms prepared in Example 1 and Comparative Examples 1 and 2. DETAILED DESCRIPTION

[0047] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] Example 1

[0049] (1) Add 10 wt% PVDF polymer powder into DMF solvent and stir at 60°C until the powder is completely dissolved to obtain a uniform and transparent slurry solution;

[0050] (2) adjusting the gap width between the scraper and the diaphragm substrate to 20 μm, then pouring the above PVDF slurry on the surface of the polypropylene (PP) diaphragm substrate, and evenly coating the slurry on the diaphragm surface with the adjusted scraper;

[0051] (3) At room temperature, ethanol was sprayed on the surface of the diaphragm just coated with PVDF slurry, with a spraying amount of 6.5 mL / m 2 , spray ethanol again after an interval of 60s, and repeat this process 4 times;

[0052] (4) The PVDF / PP membrane was dried in an oven at 80°C for 6 hours to obtain a ferroelectric coating with a thickness of 2 μm and a piezoelectric coefficient of d 33 -25pC / N, and the residual polarization intensity is 4.5μC / cm 2 In situ self-polarizing membrane.

[0053] The surface self-polarized ferroelectric coating diaphragm prepared in Example 1 was applied to a lithium-ion battery, and the high-nickel ternary NCM811 material and acetylene black were ground into a slurry at a ratio of 8:1:1 and coated on a 20μm aluminum foil as the positive electrode of the lithium-ion battery, a metal Li sheet was used as the counter electrode, and the electrolyte was 1M LiPF6 / EC+EMC+DMC (volume ratio of 1:1:1), and assembled into a CR2016 type button battery in a glove box filled with high-purity argon. The above battery was subjected to a charge and discharge cycle test under the same test equipment and test conditions, wherein the test voltage range was 2.8 to 4.3V and the test temperature was 25°C.

[0054] The electrode diaphragm was prepared by the above method, but the amount of ethanol sprayed each time was 1.0 mL / m 2 , spray ethanol again after an interval of 60s, and repeat this process 4 times;

[0055] The electrode diaphragm was prepared by the above method, but the amount of ethanol sprayed each time was 3.5 mL / m 2 , spray ethanol again after an interval of 60s, and repeat this process 4 times;

[0056] The electrode diaphragm was prepared by the above method, but the amount of ethanol sprayed each time was 8.5 mL / m 2 , spray ethanol again after an interval of 60s, and repeat this process 4 times;

[0057] The electrode diaphragm was prepared by the above method, but the amount of ethanol sprayed each time was 10.5 mL / m 2 , spray ethanol again after an interval of 60s, and repeat this process 4 times;

[0058] The electrode diaphragm was prepared by the above method, but the amount of ethanol sprayed each time was 6.5 mL / m 2 , spray ethanol again after an interval of 60s, and repeat this process once;

[0059] The electrode diaphragm was prepared by the above method, but the amount of ethanol sprayed each time was 6.5 mL / m 2 , spray ethanol again after an interval of 60s, and repeat this process twice;

[0060] The electrode diaphragm was prepared by the above method, but the amount of ethanol sprayed each time was 6.5 mL / m 2 , spray ethanol again after 60s interval, and repeat this process 3 times;

[0061] The electrode diaphragm was prepared by the above method, but the amount of ethanol sprayed each time was 6.5 mL / m 2 , spray ethanol again after an interval of 60s, and repeat this process 5 times.

[0062] When the ferroelectric coating membrane is polarized in situ using ethanol polar solvent, the polarization effects of different ethanol injection amounts and times on the ferroelectric coating are shown in Table 1 below:

[0063] Table 1

[0064]

[0065] Comparative Example 1

[0066] The battery was assembled using the method of Example 1, except that no volatile polar solvent was used to spray the diaphragm coated with PVDF slurry (ie, unpolarized-PVDF / PP diaphragm) to form a CR2016 button battery.

[0067] Comparative Example 2

[0068] The battery was assembled using the method of Example 1, except that only the same type of polypropylene separator substrate was used as the battery separator (ie, PP separator) to assemble into a CR2016 type button battery.

[0069] like Figure 1 The coating on the diaphragm obtained in Example 1 is mainly β-phase, characterized in that the CF dipoles are located on the same side, and the thickness of the ferroelectric coating on the surface of the diaphragm substrate is 2 μm ( Figure 2 ), the residual polarization intensity of the ferroelectric coating membrane is 4.5μC / cm 2 ( Figure 3 ), piezoelectric coefficient d 33 -25pC / N( Figure 4 ), and the Zeta potential of the ferroelectric coating membrane surface is -25.3mV, while the Zeta potential of the original PVDF and the membrane substrate surface is 0.13mV and 0.02mV ( Figure 5 ).

[0070] In the electrochemical test, Figure 6 It shows that the discharge capacity of the battery equipped with a surface self-polarized ferroelectric coating membrane at 0.1C is 230mAh / g, which is higher than 215mAh / g of Comparative Example 1 and 209mAh / g of Comparative Example 2; the efficiency of Example 1 is 91.8%, which is also higher than 89.7% of Comparative Example 1 and 88.3% of Comparative Example 2.

[0071] Figure 7It shows that the rate performance of the battery of Example 1 is always better than that of Comparative Examples 1 and 2, especially at a high rate of 10C, with a rate of 157.9 mAh / g, which is more obvious than 120.3 mAh / g of Comparative Example 1 and 118.1 mAh / g of Comparative Example 2. Figure 8 It shows that after 200 cycles, the capacity retention rate of Example 1 is 83.9%, which is higher than 72.3% of Comparative Example 1 and 70.2% of Comparative Example 2.

[0072] Example 2

[0073] (1) Add 5 wt% PVDF polymer powder into DMF solvent and stir at 50°C until the powder is completely dissolved to obtain a uniform and transparent slurry solution;

[0074] (2) Adjust the gap width between the scraper and the diaphragm substrate to 20 μm, then pour the above PVDF slurry on the surface of the diaphragm substrate, and use the adjusted scraper to evenly coat the slurry on the diaphragm surface;

[0075] (3) At room temperature, methanol was sprayed on the surface of the diaphragm just coated with PVDF slurry, with a spraying amount of 7.5 mL / m 2 , spray methanol again after 40s interval, and repeat this process 3 times;

[0076] (4) The PVDF / PP membrane was dried in an oven at 60°C for 4 hours to obtain a ferroelectric coating with a thickness of 1 μm and a piezoelectric coefficient of d 33 -22pC / N, and the residual polarization intensity is 2.2μC / cm 2 When the ferroelectric coating membrane is polarized in situ using methanol polar solvent, the polarization effect of different methanol injection amounts and times on the ferroelectric coating is shown in Table 2 below:

[0077] Table 2

[0078]

[0079] Example 3

[0080] (1) Add 15 wt% PVDF polymer powder into DMF solvent and stir at 80°C until the powder is completely dissolved to obtain a uniform and transparent slurry solution;

[0081] (2) Adjust the gap width between the scraper and the diaphragm substrate to 30 μm, then pour the above PVDF slurry on the surface of the diaphragm substrate, and use the adjusted scraper to evenly coat the slurry on the diaphragm surface;

[0082] (3) At room temperature, isopropanol was sprayed on the surface of the diaphragm just coated with PVDF slurry, with a spraying amount of 6.5 mL / m 2, spray isopropyl alcohol again after 90 seconds, and repeat this process 3 times;

[0083] (4) The PVDF / PP membrane was dried in an oven at 80°C for 6 hours to obtain a ferroelectric coating with a thickness of 5 μm and a piezoelectric coefficient of d 33 -20pC / N, residual polarization intensity is 1.2μC / cm 2 When the ferroelectric coating membrane is polarized in situ using isopropanol polar solvent, the polarization effect of different isopropanol injection amounts and times on the ferroelectric coating is shown in Table 3 below:

[0084] Table 3

[0085]

[0086] Example 4

[0087] (1) Add 10 wt% PVDF polymer powder into NMP solvent and stir at 60°C until the powder is completely dissolved to obtain a uniform and transparent slurry solution;

[0088] (2) Adjust the gap width between the scraper and the diaphragm substrate to 40 μm, then pour the above PVDF slurry on the surface of the diaphragm substrate, and use the adjusted scraper to evenly coat the slurry on the diaphragm surface;

[0089] (3) At room temperature, deionized water was sprayed on the surface of the diaphragm just coated with PVDF slurry by spraying, with a spraying amount of 5.0 mL / m 2 , spray deionized water again after an interval of 150s, and repeat this process 3 times;

[0090] (4) The PVDF / PP membrane was dried in an oven at 90°C for 10 hours to obtain a ferroelectric coating with a thickness of 3 μm and a piezoelectric coefficient of d 33 -24pC / N, and the residual polarization intensity is 3.8μC / cm 2 When the ferroelectric coating membrane is polarized in situ using deionized water polar solvent, the effects of different deionized water injection amounts and times on the polarization of the ferroelectric coating are shown in Table 4 below:

[0091] Table 4

[0092]

[0093]

[0094] Example 5

[0095] (1) Add 8 wt % PVDF polymer powder into NMP solvent and stir at 60° C. until the powder is completely dissolved to obtain a uniform and transparent slurry solution;

[0096] (2) adjusting the gap width between the scraper and the diaphragm substrate to 40 μm, then pouring the above PVDF slurry on the surface of the diaphragm substrate, and evenly coating the slurry on the diaphragm surface with the adjusted scraper;

[0097] (3) At room temperature, formic acid was sprayed on the surface of the diaphragm just coated with PVDF slurry, with a spraying amount of 6.0 mL / m 2 , spray formic acid again after an interval of 100s, and repeat this process 4 times;

[0098] (4) The PVDF / PP membrane was dried in an oven at 60°C for 8 hours to obtain a ferroelectric coating with a thickness of 2 μm and a piezoelectric coefficient of d 33 -18pC / N, and the residual polarization intensity is 1.8μC / cm 2 When the ferroelectric coating membrane is polarized in situ using formic acid polar solvent, the polarization effect of different formic acid injection amounts and times on the ferroelectric coating is shown in Table 5 below:

[0099] Table 5

[0100]

[0101]

[0102] Example 6

[0103] (1) Add 8 wt % PVDF polymer powder into NMP solvent and stir at 60° C. until the powder is completely dissolved to obtain a uniform and transparent slurry solution;

[0104] (2) adjusting the gap width between the scraper and the diaphragm substrate to 40 μm, then pouring the above PVDF slurry on the surface of the diaphragm substrate, and evenly coating the slurry on the diaphragm surface with the adjusted scraper;

[0105] (3) At room temperature, acetic acid was sprayed on the surface of the diaphragm just coated with PVDF slurry, with a spraying amount of 6.0 mL / m 2 , spray acetic acid again after an interval of 150s, and repeat this process twice;

[0106] (4) The PVDF / PP membrane was dried in an oven at 60°C for 8 hours to obtain a ferroelectric coating with a thickness of 2 μm and a piezoelectric coefficient of d 33 -15pC / N, residual polarization intensity is 1.5μC / cm 2 When the ferroelectric coating membrane is polarized in situ using acetic acid polar solvent, the polarization effect of different acetic acid injection amounts and times on the ferroelectric coating is shown in Table 6 below:

[0107] Table 6

[0108]

[0109]

[0110] Example 7

[0111] (1) Add 8 wt % PVDF polymer powder into NMP solvent and stir at 60° C. until the powder is completely dissolved to obtain a uniform and transparent slurry solution;

[0112] (2) Adjust the gap width between the scraper and the diaphragm substrate to 20 μm, then pour the above PVDF slurry on the surface of the diaphragm substrate, and use the adjusted scraper to evenly coat the slurry on the diaphragm surface;

[0113] (3) At room temperature, ammonia water was sprayed on the surface of the diaphragm just coated with PVDF slurry, with a spraying amount of 6.5 mL / m 2 , spray ammonia water again after an interval of 100s, and repeat this process 3 times;

[0114] (4) The PVDF / PP membrane was dried in an oven at 70°C for 6 hours to obtain a ferroelectric coating with a thickness of 2 μm and a piezoelectric coefficient of d 33 -22pC / N, and the residual polarization intensity is 3.5μC / cm 2 When the ferroelectric coating membrane is polarized in situ using ammonia polar solvent, the polarization effect of different ammonia injection amounts and times on the ferroelectric coating is shown in Table 7 below:

[0115] Table 7

[0116]

[0117] Example 8

[0118] (1) Add 8 wt % PVDF polymer powder into DMF and stir at 70° C. until the powder is completely dissolved to obtain a uniform and transparent slurry solution;

[0119] (2) Adjust the gap width between the scraper and the diaphragm substrate to 20 μm, then pour the above PVDF slurry on the surface of the diaphragm substrate, and use the adjusted scraper to evenly coat the slurry on the diaphragm surface;

[0120] (3) At room temperature, methylamine was sprayed on the surface of the diaphragm just coated with PVDF slurry, with a spraying amount of 6.5 mL / m 2 , spray methylamine again after an interval of 30 seconds, and repeat this process 4 times;

[0121] (4) The PVDF / PP membrane was dried in an oven at 70°C for 5 hours to obtain a ferroelectric coating with a thickness of 2 μm and a piezoelectric coefficient of d33 The residual polarization intensity is -23pC / N and 2.6μC / cm 2 When the ferroelectric coating membrane is polarized in situ using methylamine polar solvent, the polarization effect of different methylamine injection amounts and times on the ferroelectric coating is shown in Table 8 below:

[0122] Table 8

[0123]

[0124] Example 9

[0125] (1) Add 8 wt % PVDF polymer powder into DMF and stir at 70° C. until the powder is completely dissolved to obtain a uniform and transparent slurry solution;

[0126] (2) Adjust the gap width between the scraper and the diaphragm substrate to 20 μm, then pour the above PVDF slurry on the surface of the diaphragm substrate, and use the adjusted scraper to evenly coat the slurry on the diaphragm surface;

[0127] (3) At room temperature, ethylamine was sprayed on the surface of the diaphragm just coated with PVDF slurry, with a spraying amount of 6.0 mL / m 2 , spray ethylamine again after an interval of 50 seconds, and repeat this process 4 times;

[0128] (4) The PVDF / PP membrane was dried in an oven at 70°C for 5 hours to obtain a ferroelectric coating with a thickness of 2 μm and a piezoelectric coefficient of d 33 -22pC / N, and the residual polarization intensity is 2.5μC / cm 2 When the ferroelectric coating membrane is polarized in situ using ethylamine polar solvent, the effects of different ethylamine injection amounts and times on the polarization of the ferroelectric coating are shown in Table 9 below:

[0129] Table 9

[0130]

[0131] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.

[0132] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a battery separator capable of in-situ regulating polarization strength, characterized in that: The method comprises coating a solution containing polyvinylidene fluoride-based copolymer powder on the surface of a base film to obtain a diaphragm having a polymer coating on the surface; spraying a volatile polar solvent on the surface of the polymer coating, and waiting for the polar solvent to evaporate to obtain a diaphragm; The volatile polar solvent includes at least one of a hydroxyl-containing volatile polar solvent, a carboxyl-containing volatile polar solvent and an amino-containing volatile polar solvent; Wherein, the hydroxyl-containing volatile polar solvent includes at least one of water, methanol, ethanol, n-propanol, and isopropanol; The carboxyl-containing volatile polar solvent includes formic acid and / or acetic acid; The amino-containing volatile polar solvent includes at least one of aqueous ammonia, methylamine and ethylamine; The volatile polar solvent is sprayed at least twice, with a single spraying volume of 1-12 mL / m 2 .

2. The method for preparing a battery separator capable of in-situ regulating polarization strength according to claim 1, characterized in that: The polyvinylidene fluoride-based copolymer powder comprises at least one of PVDF, P(VDF+CTFE), P(VDF+TrFE), P(VDF+HFP) and P(VDF+TrFE+CFE); The mass concentration of the polyvinylidene fluoride based copolymer powder in the solution containing the polyvinylidene fluoride based copolymer powder is 3-15%.

3. The method for preparing a battery separator capable of in-situ regulating polarization strength according to claim 1, characterized in that: The base film includes at least one of a polyethylene film, a polypropylene film, a polyimide film, and a polypropylene / polyethylene composite film.

4. A battery separator capable of in-situ regulating polarization strength, characterized in that: The method is prepared according to any one of claims 1 to 3.

5. A battery separator capable of in-situ regulating polarization strength according to claim 4, characterized in that: The battery separator comprises a base film and a PVDF-based ferroelectric polymer coating, wherein the β-crystalline phase accounts for no less than 80% of the PVDF-based ferroelectric polymer coating.

6. Use of a battery separator with in-situ adjustable polarization strength as claimed in claim 4 or 5 as a lithium battery separator.

Citation Information

Patent Citations

  • Preparation method of PVDF-HFP / GO composite film for increasing content of beta crystalline phase

    CN107955196A

  • High-mechanical-strength, high-flame-retardant and high-adhesion battery diaphragm and preparation method thereof

    CN114374055A

  • Battery diaphragm, preparation method thereof and battery

    CN114665218A

  • PVDF piezoelectric film polarization process based on inert protective gas

    CN114899308A

  • Preparation method of polyvinylidene fluoride thin film with high beta-phase content

    CN106823858A